2009
DOI: 10.1111/igc.0b013e3181a1bf2e
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Carboplatin-Related Hypersensitivity Reactions in Japanese Patients With Gynecologic Malignancies

Abstract: Carboplatin is one of the most commonly used and well-tolerated agents for gynecologic malignancies. The rate of hypersensitivity reactions (HSRs) in the overall population of patients receiving carboplatin has been reported to increase after multiple doses of the agent. We retrospectively analyzed the incidence, clinical features, management, or outcome of carboplatin-related HSRs in 113 Japanese patients with gynecologic malignancies and the possibility of rechallenge with the drug. We intravenously administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
34
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 32 publications
(36 reference statements)
1
34
0
2
Order By: Relevance
“…3Y5 The incidence of hypersensitivity to carboplatin typically peaks from 6 to 21 cycles; symptoms frequently range from mild pruritus and erythroderma to anaphylaxis. 3Y5 Severe reactions have been observed after a cumulative dose of 8000 mg. 6 Markman et al 3Y5 reported 27% of patients developing allergic reactions after the seventh cycle. Such high rates of hypersensitivity limit further administration of carboplatin to patients with platinum-sensitive disease.…”
mentioning
confidence: 99%
“…3Y5 The incidence of hypersensitivity to carboplatin typically peaks from 6 to 21 cycles; symptoms frequently range from mild pruritus and erythroderma to anaphylaxis. 3Y5 Severe reactions have been observed after a cumulative dose of 8000 mg. 6 Markman et al 3Y5 reported 27% of patients developing allergic reactions after the seventh cycle. Such high rates of hypersensitivity limit further administration of carboplatin to patients with platinum-sensitive disease.…”
mentioning
confidence: 99%
“…Reports of hypersensitivity reactions (HSRs) to carboplatin have increased with the rise in its repetitive use in many cancer patients. Incidence of carboplatin HSR ranges from 8 to 16% (Markman et al , 1999; Polyzos et al , 2001; Koshiba et al , 2009) and can be as high as 44% in the second- and third-line settings (Morgan et al , 1994). Symptoms and signs of this allergic reaction include mild rash to diffuse erythroderma, pruritus, urticaria, angioedema, tachycardia, chest tightness, bronchospasm, dyspnea, and at the severe end, cardiopulmonary collapse.…”
mentioning
confidence: 99%
“…The reported incidence of HR in patients who received more than 7 courses of carboplatin is 26.7%, 1) which is similar to that reported previously by our group (23.2%) in patients with gynecologic cancer. 4) Although the risk of carboplatinrelated HR is thought to be associated with previous history of drug allergy, prolonged platinum-free interval or high dose of carboplatin, [2][3][4][5] these parameters are not very sensitive for the prediction of HR. Intradermal injection of carboplatin has also been used for the diagnosis of carboplatin-related HR, and the reported sensitivity and false-positivity of the test are 85.7% and 1.5%, respectively, in patients with gynecologic cancer.…”
mentioning
confidence: 99%